Effect of fibre loading on the flexural properties of natural fibre reinforced polymer composites - Mathivanan, Davindrabrabu; Siregar, Januar Parlaungan; Bachtiar, Dandi; Mohamad Ruzaimi, Mat Rejab; Cionita, Tezara (Trans Tech Publications Inc, 2015)
The use of pineapple leaf fibres as reinforcement in plastics had increased rapidly in past few years. Thus this project was conducted to determine and compare the flexural strength of pure epoxy and pineapple leaf fibres reinforced epoxy. The natural fibres were mixed with epoxy and hardener by weight percentage fibre content. The process employed to fabricate the specimens was hand lay-up and the natural fibres was oriented randomly. The dimensions of the specimens for flexure test were based on ASTM D790 respectively. The results obtained shows that 15% PALF reinforced epoxy composite achieved the highest flexural strength among the natural fibers reinforced epoxy composites.